ANALISIS PERLINDUNGAN HAK KEKAYAAN INTELEKTUAL TERHADAP SENGKETA MEREK DAGANG I AM GEPREK BENSU & GEPREK BENSU - M Albert Pribadi; Ahmad Ali Maksum; Andrea Bagus Wicaksana; Naufal Tri Brata; Ronaldo Ronaldo; Gerard Andito; Andhika Riyandi (Jurnal Jendela Hukum, 2026)
This study examines the trademark dispute of Ayam Geprek Bensu in Case Number 575 K/Pdt.Sus-HKI/2020 as an issue of intellectual property rights protection in Indonesia. The purpose of this research is to analyze the application of the first to file principle and the court’s legal considerations in resolving the trademark dispute and its implications for legal protection of business actors and consumers. The research was conducted in Indonesia with a focus on commercial court and Supreme Court decisions. This study employs a qualitative method using a case study and literature review approach. Data were collected by examining relevant laws, regulations, and judicial decisions. Findings indicate that trademark registration is the fundamental basis for legal protection, and the first to file principle ensures robust legal certainty. In conclusion, applying this principle supports fair business competition and clearer consumer protection.